Metallocene technology in commercial applications - Benedikt, George M. (Society of Plastics Engineers ; Plastics Design Library, 1999)
Second in the Metallocene series from PDL, this book focuses on the commercial use and process improvements of resins produced with metallocene, single site, and other modern catalytic methods. Research to broaden the scope of applications and shorten production cycles is presented. New and improved polymer blends resulting from the use of new catalysts and improved polymer compatability are explored as well as new applications becoming possible due to improved and balanced properties. Current trends and the latest research from the international scientific and industrial community are presented in this volume. Chapters cover use in extrusion, film manufacture, injection molding, foam production, fiber spinning, composites and new applications. Precise testing methods, material characterization, polymer morphology, and crstallization are also included.
Keywords: Metallocenes.; elektronické knihy; electronic books